Determinants of Financial Inclusion among Nigerian MSMEs: The Roles of Push Factors - Siti Shoimah; Abdullahi Adio Babatunde; Ahmed Oloruntobi Adekunle; Robby Nur Akbar (Jurnal Manajemen dan Kewirausahaan, 2025)
Financial inclusion of Micro, Small, and Medium Enterprise (MSME) owners has been identified as a vital component of the global development agenda, notably emphasized during the G20 Seoul Summit in 2020. It plays a critical role in fostering economic growth, alleviating poverty, and strengthening financial stability. However, many MSME owners remain financially excluded due to their inherent characteristics and the perceived unattractiveness of financial services. This issue is particularly prevalent in North Central Nigeria, where empirical studies are still limited. This study aims to examine the impact of key push factors on the financial inclusion of MSME owners in North Central Nigeria. The specific objectives were to investigate the effect of financial literacy, size of business, level of education, risk preference, and social network on the financial inclusion of MSME owners in this region. Using a survey design, data were collected from a stratified random sample of 435 respondents, drawn from a population of 11,607 MSME owners. The sample size was determined using the Krejcie and Morgan formula (1970). The results revealed that all five push factors have a significant positive impact on financial inclusion. The study recommends that government initiatives should prioritize financial literacy programs to enhance MSME owners' awareness and engagement with financial institutions.